Major inflammatory patterns of chronic sinonasal diseases and their accompanied anatomical variations; CT scan review - AL-Timimy, Qays Ahmed Hassan; AL-Timimy, Qays Ahmed Hassan (AL-Kindy College Medical Journal, 2015)
Background: Because of wide use of Functional Endoscopic Sinus Surgery (FESS) technique in the recent years and basic role of coronal computed tomography (CT) scan in demonstrating the normal drainage route of para-nasal sinuses, identifying the major patterns of inflammatory sinonasal disease and accompanied anatomical variations is essential for appropriate preoperative surgical planning. In review of publisthed literature, there is no data on CT patterns of chronic inflammatory sinonasal disease and their accompained anatomical variations of nose and PNS in our local population.Objectives: was to determine the frequency of CT patterns and variations in patients with sinonasal symptoms.Methods: This was a cross sectional descriptive study conducted on 404 consecutive patients with clinical manifestations of chronic rhinosinusitis referred to radiology department of Alkindy teaching hospital. Coronal and if needed axial CT scan were taken from them. CT scans were reviewed and inflammatory patterns and accompanied anatomical variations were specified.Results: Five major recurring patterns of inflammation including infundibular 23.76%, ostiomeatal unit (OMU) 21.78%, sphenoethmidal recess (SER) 7.92%, sinonasal polyposis 19.80% and sporadic 20.79% were seen. Special pattern was noted in 3.96% while normal CT examination was noted in 9.90%. The total percentage was more than 100% due to simultaneous occurance of more than one pattern in the same case. In 73.2% of cases accompanied anatomical variation including septal deviation (34%), concha bullosa (26%), Agger nasi cell (13%), giant bulla ethmoidalis (12%), Haller cell (8%), pneumatization of uncinate process (5%), paradoxic middle turbinate (4%), and Onodi cell (2%) were seen.Conclusion: In this study, the concept of the major inflammatory patterns of sinonasal disease was introduced and their frequncies in our local poluplation were reported. By applying these patterns to the radiological report, more tailored and safe endoscopic sinus surgery could be possible